Accelerating Health Reforms through Collective Action: Experiences from East Africa - Nkrumah, Yvonne (World Bank, 2015)
This publication briefly describes the processes and methodologies for building and sustaining multistakeholder coalition to drive reforms in the health sector. It is based on the experiences of three East African countries -- Uganda, Tanzania and Kenya. It outlines, by chapter, each country's experience in identifying, mobilizing, and coalescing key stakeholders to address governance bottlenecks in pharmaceutical procurement and supply chain management. It highlights challenges, successes as well as lessons learned to guide other countries.